Michał Spandowski, Catalogue of Incunabula in the National Library of Poland, in collaboration with Sławomir Szyller, description of bookbindings prepared by Maria Brynda, translation: Elżbieta Olechowska, vol. I, Warszawa: Biblioteka Narodowa 2020, s. 694 [1]. ISBN 978-83-7009-833-6 - Łukaszewski, Jakub (Biblioteka, 2021)
Recenzja: Michał Spandowski, Catalogue of Incunabula in the National Library of Poland, in collaboration with Sławomir Szyller, description of bookbindings prepared by Maria Brynda, translation: Elżbieta Olechowska, vol. I, Warszawa: Biblioteka Narodowa 2020, s. 694 [1]. ISBN 978-83-7009-833-6